Posttranscriptional deregulation of Src due to aberrant miR34a and miR203 contributes to gastric cancer development - Hao, Qiang (Korean Society for Biochemistry and Molecular Biology, 2013)
Gastric cancer remains the main cause of cancer death all around the world, and upregulated activation of the nonreceptor tyrosine kinase c-SRC (SRC) is a key player in the development. In this study, we found that expression of Src is also increased in clinical gastric cancer samples, with the protein level increased more significantly than that at the RNA level. Further study revealed that miR34a and miR203, two tumor suppressive miRNAs, inversely correlate with the expression of Src. Restoration of miR34a and miR203 decreased Src expression in gastric cancer cell lines, which in turn inhibited cell growth and cell migration. In summary, our study here revealed that posttranscriptional regulation of Src contributes to the deregulated cell growth and metastasis in gastric cancer, and targeting Src by miR34a or miR203 mimics would be a promising strategy in therapy. [BMB Reports 2013; 46(6): 316-321]